Peran Edukasi Digital Islami dalam Menyikapi Kesehatan Mental (Stres) Mahasiswa Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) - Deprizon, Deprizon; Refika, Refika; Sahlan, Sahlan; Nursyam, Ucy Rahmayani; Lestari, Afdhal; Widyanthi, Astri (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2024)
Student mental health is an important aspect that influences the quality of academic and personal life, although many studies discuss mental health, not many have contributed to the solution. The aim of this research is to determine the role of digital Islamic education in addressing mental health, especially stress, in students of the Madrasah Ibtidaiyah Education Study Program (PGMI) Muhammadiyah University of Riau. The research method uses a qualitative approach with information gathering techniques through in-depth interviews and observation. The information collected will be analyzed thematically. The results of this research provide an in-depth understanding of the ongoing impact of Islamic education on the mental health of PGMI students and provide a positive contribution to efforts to improve the mental well-being of PGMI students at Muhammadiyah University of Riau.